Long-term Gains from Electrification in Rural India - van de Walle, Dominique (Published by Oxford University Press on behalf of the World Bank, 2018)
We know surprisingly little about the long-run impacts of household electrification. This paper studies the impacts on consumption in rural India over a 17-year period, allowing for both internal and external (village-level) effects. Under our identifying assumptions, electrification brought significant consumption gains for households who acquired electricity for their own use. We also find evidence of a dynamic effect of village connectivity for households without electricity themselves. This is suggestive of an external effect, which also comes with a shift in consumption spending suggestive of status concerns among those still without electricity. Labor earnings were an important channel of impact. This was mainly through extra work by men. There was no effect on average wage rates.